Radon and thoron survey in high background radiation area at Segamat, Johor - Abd. Wahab, Nur Amira (2014)
This paper aims to present the preliminary data of radon (222Rn) and thoron (220Rn) in some high background radiation areas (HBRA) at Segamat, Johor. DOSEman PRO (SARAD GmbH, Germany) with grab sampling technique was used to measure the equilibrium equivalent concentration of radon (EECRn) and thoron (EECTn) in indoor and outdoor air during May-June 2013. Radon and thoron concentrations were monitored twelve hours every day in thirty-two locations at Segamat district. The value of EECRn ranged from 0.37 to 69.26 Bq m-3, with mean value of 13.59 Bq m-3 and 8.03 Bq m-3 for indoor and outdoor respectively. While measured values of EECTn varied from 3.43 to 27.50 Bq m-3, with mean value of 7.34 Bq m-3 and 7.21 Bq m-3 for indoor and outdoor respectively. In general, they received 3.56 mSv per year due to inhalation of radon and thoron, where indoor inhalation contribute until 2.92 mSv per year compare to only 0.64 mSv per year for outdoor.